Stabilitas Beta Indeks JII70 di Bursa Saham Indonesia Pada Pandemi Covid-19 - Andrew Reinhard Marulak Togatorop; Annisa Indira Larashati Bahari (Akuntabilitas, 2022)
COVID-19 pandemic attack all of Indonesia’s economic sectors, including stock market. One of the impacted were stocks that listed in JII70, which were index in Indonesia’s Stock Exchange that under the basis of sharia. To evaluate JII70 in handling pandemic, risk evaluation can be done, evaluation method that can be used is Rolling Beta. Beta show sensitivity of return that portfolio had against whole stock market performance. Rolling Beta itself is beta value that calculated in loop using Regression, in designated interval time, to make time series trend. Data were taken from JII70 and IHSG closing value, from May 2018–September 2022. Preliminary data analysis, using Augmented Dickey Fuller test show that JII70 and IHSG stationary before and during pandemic. Furthermore, beta analysis shows that JII70 has beta value at range 1,1–1,3 in 2018 before pandemic. However, after pandemic hit, JII70 beta value dropped, but can be maintained in 0,8–1,1. This showcase COVID-19 huge impact to Indonesia’s stock, including sharia stock, however, JII70 can rebound and maintain stable performance after pandemic going on.